Etude géologique et géotechnique du site d’un ouvrage d’art au niveau du barrage de Tabellout (PK 30+181 et PK 31+419) Wilaya de Jijel - SELMANI Besma; Dr. BENZAID Riad (Encadreur) (Université Ferhat Abbas Sétif 1. institut d'architecture et sciences de la terre. département de géologie, 2017)
As part of the realization of the future dam of Tabellout, it was decided to build an overpass 1200 m length that will be to replace and final deflection of a section of the national road 77 will be immersed the future water dam of Tabellout. The purpose of this work is to verify the feasibility of the foundations in order to provide alternatives to the service of the DTP. Variables influence our choices are the lithological nature of the site, the geometry of the proposed foundations (sheets and diameters) and the practicality of achieving these foundations. The study contains two main complementary parts, geological and geotechnical investigations. A calculation of bearing capacity of bored piles with an empirical stimate of settlement will be a guide for DTP engineers in order to make appropriate decisions regarding this project
في إطار مشروع سد تابلوط قررت إدارة الإشغال العمومية لولاية جيجل انجاز مشروع فني متمثل في جسر بطول 1200 م . لتعويض المقطع الذي ستغمره مياه السد من الطريق الوطني رقم 77 الهدف من هده الدراسة هو تحديد مدى إمكانية انجاز الأساسات الخاصة بهذا الجسر في إطار دراسة تقنية تخص البنية التحتية لهذا المنشأ الفني، وعليه تم العمل باعتبار طبيعة التربة وكذلك باقتراح عدة متغيرات فيما يخص الإبعاد الهندسية لهده الأساسات )العمق والقطر(. المذكرة تحتوي بالأخص على قسمين هامين ومتكاملين وهما جيولوجيا الموقع والجيوتقنية يث إن حساب قوة تحمل الأساسات العميقة مع حساب قيمة الهبوط تعبر معاييرهامة نأمل ان تساعد مهندسي إدارة الإشغال العمومية لولاية جيجل في أخد القرارات الصحيحة والملائمة فيما يخص هذا المشروع الفني
Keywords: Barrage de Tabellout viaduc; Faisabilité des fondations; Capacité portante.